6-12=4w-w

Simple and best practice solution for 6-12=4w-w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-12=4w-w equation:


Simplifying
6 + -12 = 4w + -1w

Combine like terms: 6 + -12 = -6
-6 = 4w + -1w

Combine like terms: 4w + -1w = 3w
-6 = 3w

Solving
-6 = 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
-6 + -3w = 3w + -3w

Combine like terms: 3w + -3w = 0
-6 + -3w = 0

Add '6' to each side of the equation.
-6 + 6 + -3w = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -3w = 0 + 6
-3w = 0 + 6

Combine like terms: 0 + 6 = 6
-3w = 6

Divide each side by '-3'.
w = -2

Simplifying
w = -2

See similar equations:

| log[5](2x)=log[5](x+6)+log[5](4) | | -7d=77 | | 6-12=4w-4 | | 15=r/-2 | | 2x-3x+6=10-14+x | | 1/6x-1/9(2x-3)=1 | | 2(4x+8)=-32 | | 8+2.5x=10+x | | 3ydx=2xdy | | 4+1/2x=13 | | 3-2a(a-1)=a(3-2a)-(2a-3) | | -20-(4h-1)=31 | | X+.06x=40 | | y=-3(x-2)(x-7) | | 19a-18a+7=-13 | | -6(2+6x)=-120 | | 3x^9y^7+6x^7y^6+9x=0 | | -5(2m-4n)= | | 1/2(8h)=36 | | 6+6(2x-1)=12x | | 2/v=1/8 | | -17=-13-6(4b+20) | | (y-8)+24=3(y-6) | | 15t+6t-11t=150 | | 7x-12x+31x+15x=+12-8 | | (x+59)+(x+51)+84=180 | | -12v+16=4(-3v+4) | | m+5-4=18 | | 5x-2=(14/3) | | 3/4b15 | | 11x-48=5x+10 | | 8n=87 |

Equations solver categories